2020
DOI: 10.1002/macp.202000041
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Reaction Conditions for Direct Arylation Polymerizations in a Sustainable Solvent

Abstract: Direct arylation polymerization (DArP) relieves the synthesis of conjugated polymers from the use of hazardous and toxic reagents typical of the traditional protocols. However, the compatibility with environmentally benign, nonhazardous, and low‐cost solvents still represents the critical aspect for projecting DArP as an industrial‐scale method for the preparation of conjugated polymers. In this study, a “green” solvent (i.e., cyclopentyl methyl ether) is implemented for the obtainment of poly(3‐hexylthiophene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…The RR gained with L1 was 90%, whereas L2 caused a high RR of 98%, consistent with Ozawa et al’s results . It was reported that the C–H bond activation may take place at the trans position in the concerted metalation–deprotonation (CMD) step. , This process will result in homocoupling and H/Br exchange thiophene species, which can subsequently be incorporated into the polymer backbone leading to T–T and H–H linkages, respectively (Figure S2). To gain insights into the effect of L1 and L2 on RR, the pathways for the formation of H–T, T–T, and H–H linkages shown in Figure S2 were examined by density functional theory (DFT) calculation (Figure ).…”
Section: Resultssupporting
confidence: 88%
“…The RR gained with L1 was 90%, whereas L2 caused a high RR of 98%, consistent with Ozawa et al’s results . It was reported that the C–H bond activation may take place at the trans position in the concerted metalation–deprotonation (CMD) step. , This process will result in homocoupling and H/Br exchange thiophene species, which can subsequently be incorporated into the polymer backbone leading to T–T and H–H linkages, respectively (Figure S2). To gain insights into the effect of L1 and L2 on RR, the pathways for the formation of H–T, T–T, and H–H linkages shown in Figure S2 were examined by density functional theory (DFT) calculation (Figure ).…”
Section: Resultssupporting
confidence: 88%
“…231 Very recently, Thompson et al also reported the first synthesis of poly(3-alkylamide thiophenes) by direct arylation polymerization in CPME as the solvent, showing M n up to 15.4 kDa and yields up to 90%, 232 as well as of other polythiophene derivatives by direct C-H bond arylation polymerization in CPME of thiophene-based monomers bearing suitable ester directing groups, in order to study the inhibition of defect formation. 233 In 2020, the homo-polymerization of 2-bromo-3-hexylthiophene, as well as the co-polymerization of a bis-thienylDPP derivative with dibromoarenes, by direct arylation reactions in CPME as sustainable reaction medium, was described by Grisorio et al 234 3.3.2. Direct C-H bond arylation of (hetero)arenes in organic carbonates.…”
Section: Direct C-h Bond Arylation Of (Hetero)arenes In Biomassderive...mentioning
confidence: 99%
“…136,150 This result demonstrates that the L1-based Pd catalytic system displays more outstanding performance in the sustainable solvent CPME. 141,143,150,151 Besides the use of 2-MeTHF and CPME, the use of bioderived solvent anisole has also emerged for DArP. 152,153 Recently, Thompson et al also identified a bio-renewable, naturally sourced aromatic solvent, p-cymene (Figure 5), in the application of DArP for the first time.…”
Section: Pd Catalysts In Sustainable Solvents and Water-compatible Conditionsmentioning
confidence: 99%